Microglia, Cytokines, and Neural Activity: Unexpected Interactions in Brain Development and Function - Ferro, Austin; Auguste, Yohan S. S.; Cheadle, Lucas (Frontiers in Immunology, 2021)
Intercellular signaling molecules such as cytokines and their receptors enable immune cells to communicate with one another and their surrounding microenvironments. Emerging evidence suggests that the same signaling pathways that regulate inflammatory responses to injury and disease outside of the brain also play powerful roles in brain development, plasticity, and function. These observations raise the question of how the same signaling molecules can play such distinct roles in peripheral tissues compared to the central nervous system, a system previously thought to be largely protected from inflammatory signaling. Here, we review evidence that the specialized roles of immune signaling molecules such as cytokines in the brain are to a large extent shaped by neural activity, a key feature of the brain that reflects active communication between neurons at synapses. We discuss the known mechanisms through which microglia, the resident immune cells of the brain, respond to increases and decreases in activity by engaging classical inflammatory signaling cascades to assemble, remodel, and eliminate synapses across the lifespan. We integrate evidence from (1) in vivo imaging studies of microglia-neuron interactions, (2) developmental studies across multiple neural circuits, and (3) molecular studies of activity-dependent gene expression in microglia and neurons to highlight the specific roles of activity in defining immune pathway function in the brain. Given that the repurposing of signaling pathways across different tissues may be an important evolutionary strategy to overcome the limited size of the genome, understanding how cytokine function is established and maintained in the brain could lead to key insights into neurological health and disease.